Comportamiento electoral de los jóvenes de 16 a 18 años del Cantón Centinela del Cóndor, Provincia de Zamora Chinchipe ante la Campaña política de la Candidata Luisa González en las elecciones anticipadas 2023 - Chuquimarca Jumbo, Luis Hernán (2024)
Currently, we can talk about a new political culture in which representative democracies, the commercialization of information and communication technologies, and their relationship with political communication and postmodernity have opted. Electoral behavior in Ecuador is a sociological phenomenon that has received little attention, which refers to the factors that influence voters when voting for democratically elected popular authorities. This is how in the year 2023 Ecuador is marked by the electoral event called by President Guillermo Lasso after the dissolution of the National Assembly, according to article 148 of the National Constitution, with elections for the Presidency, Vice-Presidency and National Assembly to conclude the constitutional period 2021-2025. Within this electoral process there are 8 candidates from different political parties, where the candidate Luisa González of the Citizen Revolution Movement is the only candidate representing the female gender, her representation highlights and breaks the paradigms as well as challenges for women in Ecuadorian politics. While its affiliation with the Citizen Revolution Movement offers a specific perspective on the country's political spectrum, its communication is carried out through social networks Facebook, TikTok, Instagram and YouTube with different communication modalities and strategies. The candidate's strategies generate an impact on the behavior of young people between 16 and 18 years old in the Centinela del Cóndor cantón, province of Zamora Chinchipe. Based on this, this research is motivated with the purpose of studying the electoral behavior of young people between 16 and 18 years old from the cantón Centinela del Cóndor, province of Zamora Chinchipe in relation to the political campaign of the candidate Luisa González for the general elections in Ecuador 2023.